Analisis Deksriptif Pembelajaran Dalam Jaringan (Online) Mahasiswa Diploma Tiga Keperawatan Universitas Ngudi Waluyo Dimasa Pandemi Covid-19 - Ana Puji Astuti; Siti Haryani; Anis Yulvita (Indonesian Journal of Nursing Research (IJNR), 2020)
Learning is the process of student interaction with lecturers and learning resources in a learning environment. Online learning becomes an option during the covid-19 pandemic to avoid direct contact with students due to covid-19. The purpose of this study is to find out the description of learning online in the students of Diploma Tiga Nursing Program Ngudi Waluyo University. This research method is descriptive with a cross sectional approach. The total of samples is 92 students. The result of the research showed that study learning plan was given before the lecture (96.7%), materials are given in accordance with the study learning plan (76.1%), there are obstacles during online learning (83.7),Â  explanation of lecture materials by lecturers can be understood (72.8%), no feedback during online learning (90.2%), Lesture assessment is conducted transparently (68.5%), media used in online learning is sipolin of Ngudi Waluyo University (50%), 43.5 % use google meet, assignment using in accordance with the study learning plan (98.9%), learning method of students center learning (95.7%). Concluded that the online learning in Diploma Three of Nursing Program of Ngudi Waluyo University went well. Suggestions for learning activities can be improved especially in the aspects of learning media that can be given in a variety.Online learningStudentCovid-19